Chemical Composition of Broiler Chicken Breast Fed Ration with Supplementation of Protected Fatty Acid - Fitrianingsih, Fitrianingsih; Tasse, A. M.; Sandiah, Natsir (Proceeding INTERNATIONAL SEMINAR IMPROVING TROPICAL ANIMAL PRODUCTION FOR FOOD SECURITY)
The experiment of protected fatty acid (PFA) supplementation in ration on chemical composition of breast broiler chicken was conducted in the field laboratory of Animal ScienceFaculty, Halu Oleo University. There were 48 broiler chickens, divided into 12 compartments stable.This experiment consist of 3 treatments were Control (100% commercial ration), DCM (+ 3% drycarboxylate salt mixture), COH ( +3% coconut oil hydrosilate), and 4 replication. The water content ofcontrol treatment was (70.5 ±1.0%), DCM (70.0 ± 0.0 %) and COH (71.5 ±1.0 %). Crude protein ofcontrol treatment was (18.26 % ± 0.38%), DCM (19.21±0.14%), and COH (18.37 ± 0.14 %). Etherextract content was 3.15 ±0.19 (control), 1.65 ± 0.13 (DCM) and 2.5 ±0.10 (COH). The data wasanalyzed by using contrast orthogonal test. The result showed that supplementation of 3 % ofprotected fatty acids in ration has significant effect (p<0.01)  on ether extract and ash broiler chickenbreast meat but has no significant effect (p>0.05) on water and the crude protein contents of broilerchicken breast meat at the age of 4 weeks old.Key Words: Chemical Composition, Protected Fatty Acid (PFA), Dry Carboxylate Salt Mixture (DCM), Coconut Oil Hydroxilase (COH)